(untitled) (Nordic Journal of African Studies, 2002)
The paper examines the Bakolori Irrigation Project in Sokoto State, Nigeria and its impact on the intended beneficiaries of the project. The paper reviewed existing irrigation types in Nigeria and implications for sustainable food security in target communities. Also, it provides an insight into the catalogue of consequences that followed the project. Some of these include farmers’ dispossessed of their productive farmlands, fraudulent reallocation processes, inadequate compensation and destruction of economic trees and crops as a result of the irrigation site. Evidences from the project shows that the project brought about certain positive developments in the lives of the target population. However, it was not devoid of undesirable challenges that require considerable attention in development project planning and implementation. These and many other issues surrounding the Bakolori irrigation project raises question on whether the project was a development or a catastrophe? Consequently, suggestions are made on how to design and implement development programmes with an overall view to improving the existing circumstances of the intended beneficiaries.